EVALUASI PROGRAM PELAKSANAAN SUPERVISI MELALUI DECRAPANCY EVALUATION MODEL (DEM) DALAM MENINGKATKAN KINERJA GURU - Jamalludin Jamalludin (STAI Sangatta Kutai Timur, 2022)
This research is an evaluation study of education in schools with the aim of improving teacher performance through the discrepancy evaluation model in carrying out supervision at SMP Negeri 2 Sangatta Utara. This research was conducted at SMP Negeri 2 Sangatta Utara with 32 teacher research subjects and the object of this research is the implementation of classroom supervision with a gap model. Research findings related to the implementation of the supervision program at SMP Negeri 2 Sangatta Utara are well done. The components that are evaluated in this component are as follows: (1) the design of the supervision program at SMP Negeri 2 Sangatta Utara has been running well, and (2) the installation of the teacher supervision program has been running well, it is necessary to improve the competence of the supervision team in participating in In House Training periodically,(3) the process of the teacher supervision program has been going well, but it is necessary to provide follow-up so that the teacher will know the shortcomings in implementing the learning process, (4) the results of the teacher supervision program are running well, the teacher is motivated to teach better, is motivated to follow various the development of the teacher's profession, namely making scientific papers for teachers to increase. The conclusion of this study is that the evaluation of the implementation of supervision with a discrepancy evaluation model can improve teacher performance at SMP Negeri 2 Sangatta Utara and develop the sustainable professional activity.